The Physician Employment Contract handbook : a guide to structuring equitable arrangements - Todd, Maria K. (New York : Productivity Press, 2011)
'This revised and updated edition provides an invaluable resource for physicians who are looking to sell their practice and for health systems who wish to become affiliated with a group practice or who are interested in contracting with physicians. The book provides sample physician employment contracts and explains how each contract works. Written by an expert in the field of physician contracting, the text discusses the various legal and compliance issues related to physician employment, such as anti-self referral and anti-kickback issues, and examines how to resolve disputes through arbitration or mediation. The author also outlines the pros and cons of various partnership arrangements'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Group medical practice -- Law and legislation -- Handbooks, manuals, etc; Physicians -- Employment -- Handbooks, manuals, etc